If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2m + -3) * 6m = 18 Reorder the terms: -2(-3 + 2m) * 6m = 18 Reorder the terms for easier multiplication: -2 * 6m(-3 + 2m) = 18 Multiply -2 * 6 -12m(-3 + 2m) = 18 (-3 * -12m + 2m * -12m) = 18 (36m + -24m2) = 18 Solving 36m + -24m2 = 18 Solving for variable 'm'. Reorder the terms: -18 + 36m + -24m2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 36m + -24m2 = 0 Factor out the Greatest Common Factor (GCF), '6'. 6(-3 + 6m + -4m2) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-3 + 6m + -4m2)' equal to zero and attempt to solve: Simplifying -3 + 6m + -4m2 = 0 Solving -3 + 6m + -4m2 = 0 Begin completing the square. Divide all terms by -4 the coefficient of the squared term: Divide each side by '-4'. 0.75 + -1.5m + m2 = 0 Move the constant term to the right: Add '-0.75' to each side of the equation. 0.75 + -1.5m + -0.75 + m2 = 0 + -0.75 Reorder the terms: 0.75 + -0.75 + -1.5m + m2 = 0 + -0.75 Combine like terms: 0.75 + -0.75 = 0.00 0.00 + -1.5m + m2 = 0 + -0.75 -1.5m + m2 = 0 + -0.75 Combine like terms: 0 + -0.75 = -0.75 -1.5m + m2 = -0.75 The m term is -1.5m. Take half its coefficient (-0.75). Square it (0.5625) and add it to both sides. Add '0.5625' to each side of the equation. -1.5m + 0.5625 + m2 = -0.75 + 0.5625 Reorder the terms: 0.5625 + -1.5m + m2 = -0.75 + 0.5625 Combine like terms: -0.75 + 0.5625 = -0.1875 0.5625 + -1.5m + m2 = -0.1875 Factor a perfect square on the left side: (m + -0.75)(m + -0.75) = -0.1875 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4w^3+3wz-8w^2-6z=0 | | 3x+6x=-15+6x | | 5x+1-4=x+7 | | y=19x^2+9x+7 | | -40=8(4p-8)-8(3+2p) | | 3x^3+x^2+6x+2=0 | | 2b+2-5b+b=180 | | 0.05x^2+1.1x=200 | | 300+0.70x=40+0.90x | | (x-14)2= | | 6+2(3j-2)=49(1+j) | | 4a^2-10a=0 | | 69.1=2*3.14*r | | 7-3(a+4)= | | t^2-7=18 | | 6y^3-21y^2-4y+14=0 | | -9=-5(8-2k)+3(k-7) | | 5x-20=10x+15 | | -5(3a+6)=-105 | | 9y=7y+24 | | 5+4t=7(t) | | -16x^2+60x=56 | | 4a+3(a-2)=2(3a-2) | | 2(4x+3)+4=3x(2x+4) | | 3(x-2)=9(9x+2) | | (-8+5i)(-7+3i)= | | 15-3(2x-9)+x=115 | | -16x^2+6x=56 | | 69.1=3.14*r | | 0.06(y-9)+0.20y=0.16y-0.01(60) | | -6.1x+108.8= | | 6(5n+7)-4(4n+6)=-24 |